Evolution of world and domestic production of internal combustion engines - Berdnychenko, Yuliia; Petrykovets, Olha (History of science and technology, 2019)
An in-depth and comprehensive study of internal combustion engines creation, the prominent figures’ contribution to the formation and development of domestic and world science, remains a crucial task of historical studies at their present stage. The steam engine did not completely solve the energy problem, the humanity was facing. Small workshops and enterprises in the 19th century, which made up a significant part of the industrial sector, were not always able to use it. The small steam engine had a low efficiency. Besides, using such an engine meant high costs and troubles. Small industry required an engine that would take up minimum space and could be turned on and off at any time without much preparation. The article is devoted to highlighting and dividing the development of gas, kerosene, gasoline and diesel engines into stages. The idea of such an engine was first proposed in the early 19th century. The prerequisites for the emergence of each engine type have been considered. The important role of Philippe Lebon as the founder of gas engine design has been shown. Several inventors from different countries worked on the idea of creating engines using various types of fuel. Among them is the Belgian engineer Jean Étienne Lenoir, who suggested starting the engine with an electric spark. The engineer Augustus Otto’s role in the development and construction of the first gas engine, which was more economical than a steam engine, has been shown. Thus, all the theoretical and constructive background for inventing a new type of internal combustion engine was there, the designer of which was Rudolf Diesel. He created and patented an internal combustion engine – “diesel”, which today remains one of the most economical heat engines.